2017
DOI: 10.1002/rth2.12009
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of refractory delayed onset heparin‐induced thrombocytopenia after thoracic endovascular aortic repair with intravenous immunoglobulin (IVIG)

Abstract: Essentials Delayed‐onset heparin‐induced thrombocytopenia can lead to severe thrombocytopenia in the setting of recent major vascular surgery.Intravenous immunoglobulin (IVIG) can be used as a supplementary treatment when platelet count fails to improve with conventional treatment.When platelet counts are severely low, benefits of using IVIG can outweigh the risks of thromboembolic events. Delayed onset heparin induced thrombocytopenia (HIT), is characterized by a late nadir due to persistent platelet‐activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
55
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(57 citation statements)
references
References 20 publications
1
55
1
Order By: Relevance
“…Only one patient had a dramatic recurrence of thrombocytopenia, despite having received two doses of IVIG (1 g/kg per dose), with an initial PLT count response (from 11 to 81) after 3 days, but then an abrupt decrease in PLT count from 81 to 5 over the next 4 days; after a third dose of IVIG (1 g/kg), the PLT count gradually increased. Interestingly, this last case was one of two patients reported by Doucette and coworkers, and both patients reported by these authors had less marked PLT count increases compared with the other patients reported. This raises the issue of whether a less effective preparation of IVIG was used in the two patients reported by Doucette and coworkers.…”
Section: Resultsmentioning
confidence: 49%
See 3 more Smart Citations
“…Only one patient had a dramatic recurrence of thrombocytopenia, despite having received two doses of IVIG (1 g/kg per dose), with an initial PLT count response (from 11 to 81) after 3 days, but then an abrupt decrease in PLT count from 81 to 5 over the next 4 days; after a third dose of IVIG (1 g/kg), the PLT count gradually increased. Interestingly, this last case was one of two patients reported by Doucette and coworkers, and both patients reported by these authors had less marked PLT count increases compared with the other patients reported. This raises the issue of whether a less effective preparation of IVIG was used in the two patients reported by Doucette and coworkers.…”
Section: Resultsmentioning
confidence: 49%
“…However, there were no clear thrombotic events identified after starting IVIG. There were two patients in whom imaging studies performed after starting IVIG showed evidence of thromboses; however, the authors did not claim that the thrombotic events occurred after IVIG administration. For example, Betrosian and colleagues noted that imaging studies performed after IVIG administration showed intraatrial thrombi and PE; however, there was no comment on interim symptoms to suggest thrombotic events occurring after IVIG administration, and given that their patient already had numerous documented events before initiation of IVIG (DVT, PE, thumb necrosis, DIC), these visualized thrombi may well have been present before starting IVIG.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…2 There are less than 20 reported cases worldwide 2 and while the triggers for its development are not known, it is believed that HIT antibodies are directed to PF4 bound to the platelet surface likely via endogenous glycosaminoglycans. 13 Intravenous immunoglobulin G (IVIG) can be strikingly effective in patients with persistent HIT refractory to non-heparin anticoagulant treatment, rapidly and durably counteracting HIT antibody-mediated platelet activation [14][15][16][17][18] and this treatment may even prevent HIT from developing in the face of heparin exposure in subacute HIT. 19 Here, we describe a severely affected patient with spontaneous HIT who was treated successfully with IVIG.…”
Section: Discussionmentioning
confidence: 99%